An alternative sensor-based method for glucose monitoring in children and young people with diabetes. Issue 6 (30th January 2017) - Edge, Julie; Acerini, Carlo; Campbell, Fiona; Hamilton-Shield, Julian; Moudiotis, Chris; Rahman, Shakeel; Randell, Tabitha; Smith, Anne; Trevelyan, Nicola
Abstract : Objective: To determine accuracy, safety and acceptability of the FreeStyle Libre Flash Glucose Monitoring System in the paediatric population. Design, setting and patients: Eighty-nine study participants, aged 4–17 years, with type 1 diabetes were enrolled across 9 diabetes centres in the UK. A factory calibrated sensor was inserted on the back of the upper arm and used for up to 14 days. Sensor glucose measurements were compared with capillary blood glucose (BG) measurements. Sensor results were masked to participants. Results: Clinical accuracy of sensor results versus BG results was demonstrated, with 83.8% of results in zone A and 99.4% of results in zones A and B of the consensus error grid. Overall mean absolute relative difference (MARD) was 13.9%. Sensor accuracy was unaffected by patient factors such as age, body weight, sex, method of insulin administration or time of use (day vs night). Participants were in the target glucose range (3.9–10.0 mmol/L) ∼50% of the time (mean 12.1 hours/day), with an average of 2.2 hours/day and 9.5 hours/day in hypoglycaemia and hyperglycaemia, respectively. Sensor application, wear/use of the device and comparison to self-monitoring of blood glucose were rated favourably by most participants/caregivers (84.3–100%). Five device related adverse events were reported across a range of participant ages. Conclusions: Accuracy, safety and user acceptability of the FreeStyle Libre System were demonstrated for the paediatric population. Accuracy of the system was unaffected by subject characteristics, making it suitable for a broad range of children and young people with diabetes. Trial registration number: NCT02388815.